Philosophy and Science in Accounting 5.0 Era : A Literature Review - Syakur, Abd.; Subiantoro, Edi; Supriadi, Bambang (Moneter: Jurnal Keuangan dan Perbankan, 2025)
The 5.0 era has introduced substantial transformations in accounting practices through the incorporation of advanced technologies, including artificial intelligence (AI), big data, and automation. These technological advancements provide enhanced efficiency and precision in financial data processing and analysis; however, they also present challenges in upholding fundamental accounting principles such as transparency, integrity, and accountability. This article analyzes the integration of technology with humanistic accounting ideals in the digital age via the lens of the philosophy of science, namely positivism, interpretivism, and pragmatism. Additionally, the article discusses the importance of ethics in accounting in the 5.0 era, emphasizing the application of virtue ethics theory and discourse to ensure that accounting decisions continue to consider relevant moral and social values. This paper advocates for a decision-making framework in accounting that emphasizes fairness, transparency, and social responsibility, notwithstanding the efficiency offered by technological advancements.